A rapid self-gelling and bioadhesive hydrogel hemostatic powder and a preparation method and application thereof
Patent Information
- Application Number
- CN202311563134.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-22
AI Technical Summary
但是在材料制备过程中,都需将羧乙基壳聚糖添加到丙烯酸单体、交联剂、N-丙烯酰氧基琥珀酰亚胺和光引发剂中引发聚合,经冷冻干燥后研磨得到成分为混合态的粉末(也就是说,对于其中的任意一个粉末颗粒,其成分往往不是单一成分,而是同时包括多种不同成分),难以实现聚丙烯酸壳聚糖粉末,聚丙烯酸粉末等各个组分的独立包装与运输,生产与存储成本较高,还会由于有效化学基团的提前反应而降低其性能
[0042]1、本发明提供的用于快速可靠止血的水凝胶粉末,既可以吸收血液中的液体并提高凝血因子的浓度,促进血凝块的形成,同时也可以在伤口处形成牢固水凝胶屏障,并紧密黏附于组织处,从而综合了各种传统止血方式的优势,凝血效果更佳。
Smart Images

Figure CN117618632B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional hemostatic materials, and more specifically, relates to a rapid self-gelling and bioadhesive hydrogel hemostatic powder, its preparation method, and its application. It can achieve rapid and reliable hemostasis and has great application prospects in the fields of medical treatment and research. It can also be used as a superabsorbent powder. Background Technology
[0002] Hemostasis aims to minimize bleeding at the patient's wound site through physical or chemical means. Effective hemostasis can reduce the likelihood of blood transfusions during medical procedures, shorten surgical time, reduce surgical risks, and decrease postoperative complications. Most existing hemostatic agents achieve hemostasis through rapid water absorption and concentration of clotting factors or through local delivery of procoagulants. However, due to the inherently gradual nature of blood clot formation, hemostasis through clotting cannot quickly control bleeding. Furthermore, blood flowing through the wound may wash away existing blood clots, limiting the effectiveness of clotting hemostasis. Adhesive sealing of the wound can overcome the shortcomings of clotting hemostasis; however, existing tissue adhesives do not have ideal adhesion, often requiring prolonged pressure or even ultraviolet irradiation to form adhesion. Moreover, when bleeding is heavy or the wound shape is very complex, tissue adhesives struggle to achieve strong adhesion and are easily washed away by blood. Compared to traditional hemostasis methods, hemostatic powder can be directly deposited on irregularly shaped, incompressible bleeding wounds, promoting hemostasis by absorbing blood. Simultaneously, hemostatic powder is convenient to carry and easy to use, making it an ideal hemostatic material. However, traditional hemostatic powders mainly stop bleeding by absorbing non-clotting components in the blood and increasing the concentration of clotting factors. They cannot form stable blood clots and may even dissolve in the blood, thus failing to stop arterial and venous bleeding.
[0003] The research group of the inventors of this invention previously obtained a rapid hemostatic hydrogel powder, its preparation method, and its application (see Chinese Patent CN114767919A). This hydrogel powder is composed of chitosan components and polyacrylic acid hydrogel components grafted with N-hydroxysuccinimide ester. This powder can rapidly absorb other components of blood. Through the intermolecular interaction between the chitosan component and the polyacrylic acid component, cross-linking is achieved by the amino groups of chitosan forming amide bonds and hydrogen bonds with the N-hydroxysuccinimide ester and carboxyl groups in the polyacrylic acid component, respectively. It then rapidly adheres to biological tissue. Compared with existing technologies, it can effectively solve the problems of poor adhesion and the need for pressure to assist in hemostasis of existing hemostatic materials. It is a green, safe, biocompatible, and tissue-adhesive hemostatic powder that achieves rapid hemostasis. Furthermore, because this hemostatic powder can effectively enhance adhesion to tissue, rapid hemostasis can be achieved without the need for pressure. However, considering the more severe and violent malignant bleeding in clinical practice, the powder needs to form stronger mechanical properties. Previous powders mainly relied on intermolecular forces between powders to gel, which had insufficient mechanical properties. Moreover, the consumption of N-hydroxysuccinimide ester would affect the reaction between the powder and amino groups on biological tissues.
[0004] The inventors of this invention previously developed a series of hemostatic materials, including an injectable hydrogel adhesive for rapid hemostasis and its preparation method and application, and a hemostatic material for rapid hemostasis and its preparation method (see Chinese patents CN114712550A and CN114887110A). These materials all utilize a polyacrylic acid hydrogel system composed of carboxyethyl chitosan and N-hydroxysuccinimide grafted onto it. However, in the material preparation process, carboxyethyl chitosan must be added to acrylic monomers, crosslinking agents, N-acryloyloxysuccinimide, and photoinitiators to initiate polymerization. After freeze-drying and grinding, a powder with a mixed composition is obtained (that is, for any given powder particle, its composition is often not a single component but includes multiple different components simultaneously). This makes it difficult to achieve independent packaging and transportation of the various components, such as polyacrylic acid chitosan powder and polyacrylic acid powder, resulting in high production and storage costs. Furthermore, the performance is reduced due to the premature reaction of effective chemical groups. Summary of the Invention
[0005] To address the aforementioned deficiencies or improvement needs of existing technologies, the present invention aims to provide a rapidly self-gelling and bioadhesive hydrogel hemostatic powder, its preparation method, and its applications. The hydrogel hemostatic (or superabsorbent) powder composition is improved by using three types of powder particles: carboxyethyl chitosan powder particles, sodium alginate oxidized powder particles, and polyacrylic acid hydrogel powder particles grafted with N-hydroxysuccinimide ester. Each powder particle is dry and has a single component (component being (i) chitosan or its derivatives, (ii) sodium alginate oxidized, and (iii) the only polyacrylic acid polymer grafted with N-hydroxysuccinimide ester). The resulting hydrogel hemostatic powder can rapidly self-gel and exhibits good bioadhesion. Compared to previously developed injectable rapid hemostatic two-component hydrogel adhesives, it provides faster hemostasis, more durable and reliable hemostatic effects, and is more convenient to use. It is suitable for emergency hemostasis and can also be used as a superabsorbent powder.
[0006] To achieve the above objectives, according to one aspect of the present invention, a hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion is provided, characterized in that the powder is in a dry state and includes a first powder particle, a second powder particle, and a third powder particle, wherein the first powder particle is chitosan or a derivative thereof powder, the second powder particle is sodium alginate oxidized powder, and the third powder particle is a polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester.
[0007] For each functional powder particle in the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion, its composition is a unique one of the following components:
[0008] (i) chitosan or its derivatives;
[0009] (ii) Oxidized sodium alginate;
[0010] (iii) Polyacrylic acid polymers grafted with N-hydroxysuccinimide ester;
[0011] In use, by applying the dry and uniformly mixed hydrogel hemostatic powder, which is capable of rapid self-gelling and bioadhesion, to the area to be hemostatically controlled, which is moist or contains flowing liquid, the powder can quickly absorb the blood in the area to be hemostatically controlled and self-gel, thereby inhibiting bleeding.
[0012] According to another aspect of the present invention, a hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion is provided, characterized in that the powder is in a dry state and includes a first powder particle, a second powder particle and a third powder particle, wherein the first powder particle is chitosan or a derivative thereof powder, the second powder particle is sodium alginate oxidized powder, and the third powder particle is a polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester.
[0013] For each functional powder particle in the aforementioned hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion, its composition is a unique one of the following components:
[0014] (i) chitosan or its derivatives;
[0015] (ii) Oxidized sodium alginate;
[0016] (iii) Polyacrylic acid polymers grafted with N-hydroxysuccinimide ester;
[0017] In use, by applying the dry and uniformly mixed hydrogel superabsorbent powder that can quickly self-gel and bio-adhere to a wet area or area with flowing liquid, it can quickly absorb the liquid in the area to be absorbed and self-gel, thereby achieving superabsorbency.
[0018] As a further preferred embodiment of the present invention, the chitosan or its derivative powder is selected from one or more of chitosan, carboxymethyl chitosan, and carboxyethyl chitosan;
[0019] Preferably, the first powder particles are carboxyethyl chitosan powder.
[0020] As a further preferred embodiment of the present invention, the mass ratio of the carboxyethyl chitosan powder, the sodium alginate oxidized powder, and the polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester satisfies (7.5-69.0):(2.3-20.7):(10.3-90.2);
[0021] Preferably, the mass ratio of the carboxyethyl chitosan powder, the sodium alginate oxidized powder, and the polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester satisfies 1:0.3:(5.2-12).
[0022] As a further preferred embodiment of the present invention, the carboxyethyl chitosan powder is synthesized by the following method:
[0023] Dissolve 1-10 wt% chitosan in acrylic acid solution and react at 20-50°C for 24-72 h. Add sodium hydroxide solution to adjust the pH to 10-13. Then dialyze the solution in deionized water to obtain carboxyethyl chitosan solution. Dry the carboxyethyl chitosan solution to obtain carboxyethyl chitosan. Grind the carboxyethyl chitosan into powder to obtain carboxyethyl chitosan powder.
[0024] Preferably, the drying includes freeze drying, direct drying of liquid, or vacuum drying after precipitation in ethanol.
[0025] As a further preferred embodiment of the present invention, the sodium alginate oxidized powder is synthesized by the following method:
[0026] Sodium alginate is dissolved in deionized water at a temperature of 10℃~25℃ to obtain a sodium alginate solution with a concentration of 1~4wt%. Then, an oxidant is added to the solution, with the amount of oxidant to sodium alginate in a mass ratio of 0.8-2. The solution is then reacted in the dark for 0.5-24 hours, followed by the addition of polyethylene glycol for 0.5-2 hours, with the amount of polyethylene glycol in a mass ratio of 1-2 to the oxidant. Finally, the solution is dialyzed in deionized water for 1-3 days, dried, and ground to obtain oxidized sodium alginate powder.
[0027] The oxidant is potassium periodate or sodium periodate, preferably sodium periodate.
[0028] As a further preferred embodiment of the present invention, the polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester is synthesized by the following method:
[0029] A photoinitiator, crosslinking agent, N-acryloyloxysuccinimide, and monomer are dissolved in deionized water and polymerized under ultraviolet light. The resulting product is then dried and ground to obtain a polyacrylic acid polymer powder of N-hydroxysuccinimide ester. The monomer is an acrylic acid monomer, and the crosslinking agent is preferably methacrylated gelatin.
[0030] Alternatively, a pregel solution is obtained by first dissolving a photoinitiator, a crosslinking agent, N-acryloyloxysuccinimide, and a monomer in deionized water, then pouring the pregel solution into a template and crosslinking it under ultraviolet light to form a hydrogel, followed by drying and grinding; wherein the monomer is an acrylic monomer, and the crosslinking agent is preferably methacrylated gelatin.
[0031] According to another aspect of the present invention, a method for preparing the above-mentioned hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion, or the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion, is provided, characterized by comprising the following steps:
[0032] The steps for preparing carboxyethyl chitosan powder are as follows: 1-10 wt% chitosan is dissolved in an acrylic acid solution and reacted at 20-50°C for 24-72 h. Sodium hydroxide solution is added to adjust the pH to the range of 10-13. Then, the solution is dialyzed in deionized water to obtain a carboxyethyl chitosan solution. The carboxyethyl chitosan solution is then dried and ground into powder to obtain carboxyethyl chitosan powder. Preferably, the drying includes freeze drying, direct drying of liquid, or vacuum drying after precipitation in ethanol.
[0033] The steps for preparing oxidized sodium alginate powder are as follows: Sodium alginate is dissolved in deionized water at a temperature of 10℃~25℃ to obtain a sodium alginate solution with a concentration of 1~4wt%. Then, an oxidizing agent is added to the solution, and the mass ratio of the oxidizing agent to the sodium alginate is 0.8-2. The solution is then reacted in the dark for 0.5-24 hours. Polyethylene glycol is then added and reacted for 0.5-2 hours, and the mass ratio of the polyethylene glycol to the oxidizing agent is 1-2. Finally, the solution is dialyzed in deionized water for 1-3 days, dried, and ground to obtain oxidized sodium alginate powder.
[0034] The steps for preparing polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester are as follows: First, a photoinitiator, a crosslinking agent, N-acryloyloxysuccinimide, and a monomer are dissolved in deionized water, and a polymerization reaction is carried out under ultraviolet light. Then, the mixture is dried and ground to obtain the polyacrylic acid polymer powder of N-hydroxysuccinimide ester. The monomer is an acrylic acid monomer.
[0035] Preferably, the process further includes a mixing step: mixing the carboxyethyl chitosan powder, the oxidized sodium alginate powder, and the N-hydroxysuccinimide ester polyacrylic acid polymer powder in a dry state.
[0036] According to another aspect of the present invention, the application of the above-mentioned hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion in the preparation of medical hemostatic materials is provided, or the application of the above-mentioned hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion as a superabsorbent powder is provided.
[0037] As a further preferred embodiment of the present invention, the medical hemostatic material is obtained by attaching the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion to the surface of a carrier.
[0038] Compared with the prior art, the hydrogel hemostatic (or superabsorbent) powder of the present invention, which is capable of rapid self-gelling and bioadhesion, is in a dry state and mainly consists of three types of single-component powder particles: chitosan derivative (or chitosan) powder, sodium alginate oxidized powder, and polyacrylic acid hydrogel powder. The chitosan derivative can be, for example, carboxyethyl chitosan obtained by reacting acrylic acid with high-viscosity chitosan. The polyacrylic acid hydrogel is grafted with N-hydroxysuccinimide ester. For any one of the powder particles, its component is (i) chitosan or its derivative, (ii) sodium alginate oxidized powder, or (iii) a polyacrylic acid polymer grafted with N-hydroxysuccinimide ester. Taking its application in hemostasis as an example (the application of superabsorbent hydrogels is similar), during use, the uniformly mixed hydrogel powder (while still dry) is applied to the bleeding site. The powder rapidly absorbs non-clotting components from the blood, increasing the concentration of clotting factors. Simultaneously, it gels at the bleeding site, forming a strong physical barrier, thereby achieving rapid and reliable hemostasis. The hydrogel powder of this invention has a simple preparation process, achieves synergistic hemostasis at both chemical and physical levels, and also possesses good biocompatibility.
[0039] Taking hemostasis as an example, the hydrogel powder for rapid and reliable hemostasis obtained by this invention is mainly composed of three single-component powder particles: chitosan or its derivatives (e.g., carboxyethyl chitosan), sodium alginate oxidized powder, and polyacrylic acid hydrogel powder grafted with N-hydroxysuccinimide ester. For example, it may include 7.5-69.0 wt% carboxyethyl chitosan, 2.3-20.7 wt% sodium alginate oxidized, and 10.3-90.2 wt% N-acryloyloxysuccinimide-grafted polyacrylic acid. When the powder is used as a whole, the amino groups in the carboxyethyl chitosan can undergo a Schiff base reaction with the aldehyde groups in the sodium alginate oxidized, promoting the formation of a network structure hydrogel in the liquid environment, accelerating the aggregation of clotting factors in the blood, promoting coagulation, and forming a strong, self-healing physical barrier at the wound site, which can further promote coagulation. N-hydroxysuccinimide ester grafted onto polyacrylic acid can undergo transesterification with groups on the tissue, enabling the formed hydrogel barrier to maintain strong adhesion to the tissue, thereby achieving long-term, stable wound sealing and hemostasis.
[0040] The hydrogel hemostatic powder obtained by this invention has better mechanical properties. Unlike the previous work CN114767919A, this invention not only contains a polyacrylic acid hydrogel component grafted with N-hydroxysuccinimide ester and a chitosan component, but each powder particle also has a single component, which does not react prematurely in the dry state, avoiding the problem of premature consumption of N-hydroxysuccinimide ester by the chitosan component. Furthermore, sodium alginate powder is introduced into the powder, and all three types of particles can be ground into a powder state with uniform particle size. Therefore, the powder of this invention can not only undergo intermolecular interactions between the chitosan component and the polyacrylic acid component, but the aldehyde groups in sodium alginate oxidase can also react with the amine groups in the chitosan component to form Schiff bases, thereby improving the mechanical properties of the powder after gel formation. The rapid self-gelling and bioadhesive hydrogel hemostatic powder obtained in this invention, compared with the previously developed rapid hemostatic hydrogel powder (CN114767919A), has an added cross-linking network in terms of mechanical design. Moreover, it and the other two materials are all powder components. During use, the uniformly mixed powder can ensure the formation of a uniform hydrogel, improving the uniformity of the hydrogel and thus effectively improving its mechanical properties. In terms of material synthesis method, the three active ingredients are effectively separated in advance through drying, avoiding the self-consumption of active ingredients during storage. This makes the rapid self-gelling and bioadhesive hydrogel hemostatic powder of this invention a hydrogel hemostatic powder with long-lasting and reliable hemostatic effect, more convenient to use, more in line with doctors' usage habits, and suitable for emergency hemostasis.
[0041] Compared with traditional hemostatic materials, the present invention has the following advantages:
[0042] 1. The hydrogel powder for rapid and reliable hemostasis provided by this invention can absorb liquid in the blood and increase the concentration of clotting factors, promoting the formation of blood clots. At the same time, it can form a strong hydrogel barrier at the wound site and adhere tightly to the tissue, thus combining the advantages of various traditional hemostasis methods and achieving better hemostasis effect.
[0043] 2. The physical barrier formed by this hydrogel powder at the wound site is very strong and can withstand great pressure. At the same time, the hydrogel barrier has a self-healing function. Even if it breaks due to special circumstances, it can heal after a certain period of time and continue to maintain its strong performance.
[0044] 3. This hydrogel powder is easy to use and can be applied to hemostasis in various treatment situations and for various types of wounds. Moreover, it uses a small molecule cross-linking agent, which degrades quickly.
[0045] 4. The development of this hydrogel powder provides new ideas for the development of various subsequent therapeutic drugs. Adding hemostatic agents to the powder can further enhance its hemostatic ability, and adding antibiotics and other drugs can achieve anti-inflammatory and bactericidal effects on wounds.
[0046] 5. The challenge of hemostatic hydrogel powder compared to injectable hemostatic hydrogels and hemostatic hydrogel patches lies in improving its mechanical properties, as the hydrogel powder particles need to form a monolithic hydrogel through the self-healing properties of the hydrogel. To overcome this challenge, taking carboxyethyl chitosan as an example, this invention allows the simultaneous use of polyacrylic acid, sodium alginate with aldehyde groups, and carboxyethyl chitosan with amino groups. Hydrogen bonding and Schiff base reactions impart self-healing properties to the material. By adjusting the ratio of the three components, the cohesive energy of the material itself and the adhesion strength at the interface can be optimized, thereby achieving the best mechanical properties at the hydrogel-biological tissue interface. In the hemostatic hydrogel powder of this invention, the optimal mass ratio of carboxyethyl chitosan powder, sodium alginate powder, and polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester is 1:0.3:(5.2-12).
[0047] 6. Grafting N-hydroxysuccinimide ester onto polyacrylic acid to achieve adhesion. To meet different in vivo requirements, varying degrees of adhesion and blood absorption rates can be achieved by adjusting the content of N-hydroxysuccinimide ester. For example, to achieve strong adhesion, as much N-hydroxysuccinimide ester as possible needs to be grafted. However, excessively high ester content can affect the polymerization of the acrylic acid solution to form a hydrogel, and also affect the blood absorption rate and volume of the powder, which is detrimental to achieving a high blood absorption rate. Therefore, based on this invention, the characteristics of strong adhesion and high blood absorption rate can be achieved by adjusting the ratio. Attached Figure Description
[0048] Figure 1 This is a functional schematic diagram of the hydrogel powder for rapid hemostasis according to the present invention.
[0049] Figure 2 This is a photograph of the hydrogel powder and spraying device for rapid hemostasis according to the present invention.
[0050] Figure 3 This is the water absorption result of the hydrogel powder that can quickly stop bleeding, as described in Example 2 of the present invention.
[0051] Figure 4 This is Example 4 of the present invention, which demonstrates the in vitro hemostatic effect of a hydrogel powder that can rapidly stop bleeding.
[0052] Figure 5 This is Example 3 of the present invention, which describes the hemostatic effect of a hydrogel powder that can quickly stop bleeding on a partial liver resection wound in a rat. Detailed Implementation
[0053] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0054] The carboxyethyl chitosan used in the following examples was synthesized as follows: 2g of chitosan was poured into 100ml of deionized water, and 2.92ml of acrylic acid was added while stirring rapidly. After the chitosan was completely dissolved, the solution was placed in an oil bath at 50℃ and reacted for 72h. The pH was adjusted to the range of 10-13 with 1mol / L sodium hydroxide solution. The solution was then transferred to a dialysis bag and dialyzed in deionized water for 72h. Finally, the solution was freeze-dried and ground into powder to obtain carboxyethyl chitosan powder.
[0055] The sodium alginate oxide used in the following examples was synthesized as follows: 4g of sodium alginate was dissolved in 100g of water, stirred until homogeneous, and then 2g of sodium periodate was added. The reaction was carried out at room temperature under light-protected conditions for 24 hours, and then 3g of ethylene glycol was added to terminate the reaction. The resulting solution was transferred to a dialysis bag and dialyzed for 72 hours. After freeze-drying, it was ground into powder, and the resulting powder was sodium alginate oxide powder.
[0056] The N-acryloyloxysuccinimide-grafted polyacrylic acid used below was synthesized as follows: 0.05 g of photoinitiator (2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone), 0.01 g of methacrylated gelatin, and 0.2 g of N-acryloyloxysuccinimide were dissolved in 10 g of a 20% (w / w) acrylic acid solution. The solution was poured into a template and irradiated under 200 W ultraviolet light for 60 minutes to obtain an N-acryloyloxysuccinimide-grafted polyacrylic acid hydrogel. The hydrogel was freeze-dried and ground to obtain an N-acryloyloxysuccinimide-grafted polyacrylic acid powder.
[0057] The following are specific examples:
[0058] Example 1
[0059] In this embodiment, the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion includes dry and separated carboxyethyl acrylic acid powder (i.e., the first powder portion), sodium alginate oxidized powder (i.e., the second powder portion), and N-acryloyloxysuccinimide grafted polyacrylic acid powder (i.e., the third powder portion); the mass ratio of the three is 1:0.3:0.15.
[0060] When using, mix these three powders thoroughly in a dry state.
[0061] Example 2
[0062] In this embodiment, the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion includes dried and separated carboxyethyl acrylic acid (i.e., the first powder portion), sodium alginate oxide (i.e., the second powder portion), and N-acryloyloxysuccinimide-grafted polyacrylic acid (i.e., the third powder portion); the mass ratio of the three is 1:0.3:1.3.
[0063] When using, mix these three powders thoroughly in a dry state.
[0064] Example 3
[0065] In this embodiment, the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion includes dried and separated carboxyethyl acrylic acid (i.e., the first powder portion), sodium alginate oxide (i.e., the second powder portion), and N-acryloyloxysuccinimide-grafted polyacrylic acid (i.e., the third powder portion); the mass ratio of the three is 1:0.3:12.
[0066] When using, mix these three powders thoroughly in a dry state.
[0067] Example 4
[0068] In this embodiment, the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion includes dried and separated carboxyethyl acrylic acid (i.e., the first powder portion), sodium alginate oxide (i.e., the second powder portion), and N-acryloyloxysuccinimide-grafted polyacrylic acid (i.e., the third powder portion); the mass ratio of the three is 1:0.3:5.2.
[0069] When using, mix these three powders thoroughly in a dry state.
[0070] Example 5
[0071] In this embodiment, the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion includes dried and separated carboxyethyl acrylic acid (i.e., the first powder portion), sodium alginate oxide (i.e., the second powder portion), and N-acryloyloxysuccinimide-grafted polyacrylic acid (i.e., the third powder portion); the mass ratio of the three is 1:0.3:0.33.
[0072] When using, mix these three powders thoroughly in a dry state.
[0073] Comparative Example 1
[0074] This comparative example uses only N-acryloyloxysuccinimide-grafted polyacrylic acid powder.
[0075] Comparative Example 2
[0076] At room temperature, 0.4g of carboxyethyl chitosan was dissolved in 6.6g of deionized water, and 3g of acrylic acid, 0.01g of methacrylic anhydride gelatin, 0.1g of N-acryloyloxysuccinimide, and 0.05g of α-ketoglutaric acid were added. The mixture was reacted under UV light for 1 hour, freeze-dried, and freeze-ground into powder.
[0077] Comparative Example 3
[0078] At room temperature, carboxyethyl chitosan, sodium alginate, and N-acryloyloxysuccinimide-grafted polyacrylic acid were dissolved in deionized water at a mass ratio of 1:0.3:12. After mixing evenly and allowing to stand at room temperature until completely gelled, the mixture was freeze-dried and freeze-ground to obtain powder.
[0079] Comparative Example 4
[0080] At room temperature, dissolve 2g of carboxyethyl chitosan in 100ml of water, then add 30g of acrylic acid and let stand overnight. Take 20g of the above solution, add 0.01g of methacrylic anhydride gelatin, 0.05g of α-ketoglutaric acid, and 0.4g of N-acryloyloxysuccinimide, and stir until transparent. Pour into an acrylic mold and crosslink in a UV crosslinking chamber for 30min. Freeze-dry and freeze-mill into powder.
[0081] The hemostatic properties of the powders obtained in the examples and comparative examples were tested using anticoagulated pig blood. The gelation time and 24-hour blood absorption rate were measured by immersing the powder in anticoagulated pig blood. The results are shown in Table 1. Furthermore, pigskin was fixed to the surface of an iron can to form a closed chamber. A 2mm hole was made in the surface of the pigskin, and the corresponding powder was sprinkled into the hole, followed by the addition of PBS solution. To more closely approximate the real-world situation, a large amount of PBS solution was added to the outside of the powder to ensure complete swelling. After swelling reached equilibrium, the chamber was pressurized, and the maximum pressure was measured using a pressure gauge; this was the burst strength. Pigskin was soaked in anticoagulated pig blood until it absorbed the blood, and then the corresponding powder was sprinkled on it. Two pigskins were then bonded together, and the bonded pigskins were completely immersed in PBS solution at 37°C until fully swollen. A 180-degree peel test was then performed using a tensile testing machine, and the maximum force required to pull the two pigskins apart was measured. This force divided by the width of the pigskin was the adhesive strength. The burst strength and adhesive strength results are shown in Table 2.
[0082] Table 1. Comparison of rapid hemostasis performance between the experimental group and the control group.
[0083]
[0084] Table 2. Comparison of hemostatic performance between the experimental group and the control group
[0085]
[0086]
[0087] The hemostatic powder of this invention, compared to Comparative Example 1, can rapidly absorb blood at the site of blood tissue and then form a gel in situ. Compared to Comparative Example 4, Example 3 has a similar polyacrylic acid content but exhibits a higher blood absorption rate (as shown in Table 1). Examples 2-5, compared to Comparative Examples 1-3, show higher burst strength and adhesion strength after the hydrogel is fully swollen (Table 2), demonstrating the ability to achieve strong hemostasis and wound sealing. The optimized Example 3, compared to Comparative Example 4, exhibits higher burst strength and adhesion strength after the hydrogel is fully swollen, thereby improving the mechanical properties of the powder after gel formation and enhancing interfacial strength.
[0088] Based on the hydrogel hemostatic powder with rapid self-gelling and bioadhesion obtained by this invention, the three powders (i.e., chitosan or its derivative powder, sodium alginate oxidized powder, and polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester) can be prepared separately, stored and transported independently, and then mixed uniformly in a dry state before use. Alternatively, they can be directly mixed in a dry state to obtain a uniform powder (for the mixed powder, each powder particle remains a single component, i.e., either chitosan or its derivative powder, sodium alginate oxidized powder, or polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester, with a single component). In practical use, such as... Figure 1 As shown, hemostatic powder can be delivered to the bleeding site via a powder delivery device. The powder particles absorb the liquid components in the blood and swell into hydrogel microspheres. These microspheres then self-heal upon contact, forming a solid hydrogel barrier. Hydrogen bonds and N-acryloyloxysuccinimide bonds on the hydrogel surface react with amino groups on the tissue surface to form adhesion. Ultimately, a tightly adhered and robust barrier is formed on the tissue surface, achieving powerful hemostasis.
[0089] Powder sprayer, such as Figure 2 As shown, it consists of a powder storage chamber and a powder delivery conduit. For example, the powder obtained in Example 1 can be mixed and loaded into the powder sprayer. The powder storage chamber is disc-shaped, flexible and deformable. By pressing it with your hand, the space of the powder storage chamber is reduced and the pressure is increased. Under the action of pressure, the powder flows from the outlet of the powder storage chamber through the long conduit to the bleeding point, thereby realizing the delivery of powder.
[0090] The powder obtained in Example 2 was mixed and added to anticoagulated pig blood. After a certain period of time, the solid components were removed and weighed to obtain the amount of blood absorbed by the powder. The results are as follows: Figure 3 As shown, the powder reaches saturation in about 60 seconds and can absorb nearly 20 times its own weight in blood.
[0091] The powder obtained in Example 4 was mixed and added to a centrifuge tube containing anticoagulated pig blood. After 10 seconds, the centrifuge tube was inverted (corresponding to...). Figure 4 (See the right image in the image). Meanwhile, anticoagulated pig blood without any added powder was used as a control (corresponding to...). Figure 4 (Left figure in the image). The result is as follows: Figure 4 As shown, the anticoagulant pig blood without added powder cannot form a stable blood clot, while the powder in Example 4 can react with the blood and form a stable blood clot, indicating that Example 4 has obvious hemostatic and coagulation properties.
[0092] The powder obtained in Example 3 was mixed and sprayed onto the bleeding wound in the liver of mice. The immediate results upon contact with the tissue were as follows: Figure 5 As shown, the bleeding at the wound site stopped, demonstrating that the hemostatic powder has a good hemostatic effect in animals.
[0093] The above embodiments are based on hemostatic applications. Besides being used as a hemostatic powder, the powder obtained by this invention can also be used as a superabsorbent powder. Of course, based on this invention, in addition to the three functional powder particles—chitosan or its derivative powder particles (i.e., the first powder particle), sodium alginate oxidized powder particles (the second powder particle), and polyacrylic acid polymer powder particles grafted with N-hydroxysuccinimide ester (the third powder particle)—other types of solid particles, such as particles of other pharmaceutical excipients, may be added.
[0094] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion, characterized in that, The powder is in a dry state and includes a first powder particle, a second powder particle, and a third powder particle. The first powder particle is carboxyethyl chitosan powder, the second powder particle is sodium alginate oxidized powder, and the third powder particle is a polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester. For each functional powder particle in the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion, its composition is a unique one of the following components: (i) Carboxyethyl chitosan; (ii) Oxidized sodium alginate; (iii) Polyacrylic acid polymers grafted with N-hydroxysuccinimide ester; The mass ratio of the carboxyethyl chitosan powder, the sodium alginate oxidized powder, and the polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester satisfies 1:0.3:(5.2-12). In use, by applying the dry and uniformly mixed hydrogel hemostatic powder, which is capable of rapid self-gelling and bioadhesion, to the area to be hemostatically controlled, which is moist or contains flowing liquid, the powder can quickly absorb the blood in the area to be hemostatically controlled and self-gel, thereby inhibiting bleeding.
2. A hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion, characterized in that, The powder is in a dry state and includes a first powder particle, a second powder particle, and a third powder particle. The first powder particle is carboxyethyl chitosan powder, the second powder particle is sodium alginate oxidized powder, and the third powder particle is a polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester. For each functional powder particle in the aforementioned hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion, its composition is a unique one of the following components: (i) Carboxyethyl chitosan; (ii) Oxidized sodium alginate; (iii) Polyacrylic acid polymers grafted with N-hydroxysuccinimide ester; The mass ratio of the carboxyethyl chitosan powder, the sodium alginate oxidized powder, and the polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester satisfies 1:0.3:(5.2-12). In use, by applying the dry and uniformly mixed hydrogel superabsorbent powder that can quickly self-gel and bio-adhere to a wet area or area with flowing liquid, it can quickly absorb the liquid in the area to be absorbed and self-gel, thereby achieving superabsorbency.
3. The hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion as described in claim 1, or the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion as described in claim 2, characterized in that, The carboxyethyl chitosan powder was synthesized using the following method: Dissolve 1-10 wt% chitosan in acrylic acid solution and react at 20-50℃ for 24-72 h. Add sodium hydroxide solution to adjust the pH to 10-13. Then dialyze the solution in deionized water to obtain carboxyethyl chitosan solution. Dry the carboxyethyl chitosan solution to obtain carboxyethyl chitosan. Grind the carboxyethyl chitosan into powder to obtain carboxyethyl chitosan powder.
4. The hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion as described in claim 3, or the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion, characterized in that... The drying process includes freeze drying, direct drying of liquid, or vacuum drying after precipitation in ethanol.
5. The hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion as described in claim 1, or the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion as described in claim 2, characterized in that, The sodium alginate powder is synthesized using the following method: Sodium alginate is dissolved in deionized water at a temperature of 10℃~25℃ to obtain a sodium alginate solution with a concentration of 1~4wt%. Then, an oxidant is added to the solution, with the amount of oxidant to sodium alginate in a mass ratio of 0.8-2. The solution is then reacted in the dark for 0.5-24 hours, followed by the addition of polyethylene glycol for 0.5-2 hours, with the amount of polyethylene glycol in a mass ratio of 1-2 to the oxidant. Finally, the solution is dialyzed in deionized water for 1-3 days, dried, and ground to obtain oxidized sodium alginate powder. The oxidant is potassium periodate or sodium periodate.
6. The hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion as described in claim 1, or the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion as described in claim 2, characterized in that, The polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester was synthesized by the following method: A photoinitiator, crosslinking agent, N-acryloyloxysuccinimide, and monomer are dissolved in deionized water, and a polymerization reaction is carried out under ultraviolet light. The product is then dried and ground to obtain a polyacrylic acid polymer powder of N-hydroxysuccinimide ester. The monomer is an acrylic acid monomer. Alternatively, a pregel solution is obtained by first dissolving a photoinitiator, a crosslinking agent, N-acryloyloxysuccinimide, and a monomer in deionized water, then pouring the pregel solution into a template and crosslinking it under ultraviolet light to form a hydrogel, followed by drying and grinding; wherein the monomer is an acrylic monomer.
7. The hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion as described in claim 6, or the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion, characterized in that... The crosslinking agent is methacrylated gelatin.
8. The method for preparing the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion as described in any one of claims 1, 3-7, characterized in that, Includes the following steps: The steps for preparing carboxyethyl chitosan powder are as follows: 1-10 wt% chitosan is dissolved in an acrylic acid solution and reacted at 20-50℃ for 24-72 h. Sodium hydroxide solution is added to adjust the pH to the range of 10-13. Then, the solution is dialyzed in deionized water to obtain a carboxyethyl chitosan solution. After drying the carboxyethyl chitosan solution, it is ground into powder to obtain carboxyethyl chitosan powder. The steps for preparing oxidized sodium alginate powder are as follows: Sodium alginate is dissolved in deionized water at a temperature of 10℃~25℃ to obtain a sodium alginate solution with a concentration of 1~4wt%. Then, an oxidizing agent is added to the solution, and the mass ratio of the oxidizing agent to the sodium alginate is 0.8-2. The solution is then reacted in the dark for 0.5-24 hours. Polyethylene glycol is then added and reacted for 0.5-2 hours, and the mass ratio of the polyethylene glycol to the oxidizing agent is 1-2. Finally, the solution is dialyzed in deionized water for 1-3 days, dried, and ground to obtain oxidized sodium alginate powder. The steps for preparing polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester are as follows: First, a photoinitiator, a crosslinking agent, N-acryloyloxysuccinimide and a monomer are dissolved in deionized water, and a polymerization reaction is carried out under ultraviolet light. Then, the mixture is dried and ground to obtain polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester. The monomer is an acrylic acid monomer.
9. The method for preparing the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion as described in any one of claims 2-7, characterized in that, Includes the following steps: The steps for preparing carboxyethyl chitosan powder are as follows: 1-10 wt% chitosan is dissolved in an acrylic acid solution and reacted at 20-50℃ for 24-72 h. Sodium hydroxide solution is added to adjust the pH to the range of 10-13. Then, the solution is dialyzed in deionized water to obtain a carboxyethyl chitosan solution. After drying the carboxyethyl chitosan solution, it is ground into powder to obtain carboxyethyl chitosan powder. The steps for preparing oxidized sodium alginate powder are as follows: Sodium alginate is dissolved in deionized water at a temperature of 10℃~25℃ to obtain a sodium alginate solution with a concentration of 1~4wt%. Then, an oxidizing agent is added to the solution, and the mass ratio of the oxidizing agent to the sodium alginate is 0.8-2. The solution is then reacted in the dark for 0.5-24 hours. Polyethylene glycol is then added and reacted for 0.5-2 hours, and the mass ratio of the polyethylene glycol to the oxidizing agent is 1-2. Finally, the solution is dialyzed in deionized water for 1-3 days, dried, and ground to obtain oxidized sodium alginate powder. The steps for preparing polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester are as follows: First, a photoinitiator, a crosslinking agent, N-acryloyloxysuccinimide and a monomer are dissolved in deionized water, and a polymerization reaction is carried out under ultraviolet light. Then, the mixture is dried and ground to obtain polyacrylic acid polymer powder grafted with N-hydroxysuccinimide ester. The monomer is an acrylic acid monomer.
10. The preparation method according to claim 8 or 9, characterized in that, In the step of preparing carboxyethyl chitosan powder, the drying includes freeze drying, direct drying in liquid, or vacuum drying after precipitation in ethanol.
11. The preparation method according to claim 8 or 9, characterized in that, It also includes a mixing step: mixing the carboxyethyl chitosan powder, the oxidized sodium alginate powder, and the N-hydroxysuccinimide ester polyacrylic acid polymer powder in a dry state.
12. The application of the hydrogel hemostatic powder capable of rapid self-gelling and bioadhesion as described in any one of claims 1, 3-7 in the preparation of medical hemostatic materials.
13. The application as described in claim 12, characterized in that, The medical hemostatic material is obtained by attaching the hydrogel hemostatic powder, which is capable of rapid self-gelling and bioadhesion, to the surface of a carrier.
14. The application of the hydrogel superabsorbent powder capable of rapid self-gelling and bioadhesion as described in any one of claims 2-7 as a superabsorbent powder.
Citation Information
Patent Citations
Injectable hydrogel adhesive capable of rapidly stopping bleeding as well as preparation method and application of injectable hydrogel adhesive
CN114712550A
Hydrogel powder for rapid hemostasis and preparation method and application thereof
CN114767919A
Hemostatic material capable of rapidly stopping bleeding and preparation method thereof
CN114887110A